Estimation of flooded areas on Frío river basin (Costa Rica) using polarimetry with synthetic aperture radar (SAR) of Sentinel 1A imagery - Martínez-Barbáchano, Rubén (Revista Geográfica de América Central., 2022)
Synthetic Aperture Radar (SAR) polarimetry is a remote sensing technique known for being applied to monitoring of land surface and water bodies. Polarimetry aims at charactering the land surface through the analysis of its response under different combinations of transmitting and receiving an- tennas polarization, called polarimetric channels. The use of cross-polarization (vertical/horizontal) proved to be efficient for estimating the extent of the floods between July 22nd and July 30th in the Frío river basin (Costa Rica). To that end, Sentinel-1 images from the European Space Agency have been used, with a workflow process and RGB composition that allowed to draw a clear distinction between flooded and permanent water bodies. The use of optical imagery for flood mapping is limit- ed by weather conditions, specially by the presence of clouds. SAR measurements are independent of daytime and weather conditions, providing valuable information for monitoring flood events. Furthermore, flood extent is a critical factor for the calibration and validation of hydraulic models (Horritt, 2006). Flood extent can be also used for damage assessment and risk management and can be of benefit to rescuers during flooding (Corbley, 1999).